2021
DOI: 10.1007/s10750-021-04577-y
|View full text |Cite
|
Sign up to set email alerts
|

Trading offspring for survival: high duckweed cover decreases reproductive potential and stimulates elongation in the submerged macrophyte Chara globularis Thuillier

Abstract: Compact blankets of free-floating plants generate stressful aquatic environments. The response of submerged macrophytes remains largely elusive. Will they rush toward the light or rather speed up reproductive efforts and escape using propagules—the macrophyte equivalent of lifeboats? We studied the effects of complete duckweed (Lemna minor) cover on growth and reproductive fitness of macroalga Chara globularis in a pond mesocosm experiment. C. globularis growing in Lemna-covered plots lost biomass and develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Total Phosphorus concentration decreased slightly, and dissolved oxygen increased by 1019% from pre-removal period (Ronkainen, 2021). A study that focused on Chara globularis, a common, eutrophication-tolerant macroalga, found L. minor domination to inhibit growth of C. globularis and potentially lead to a gradual decline of its overall population (Van Onsem et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Total Phosphorus concentration decreased slightly, and dissolved oxygen increased by 1019% from pre-removal period (Ronkainen, 2021). A study that focused on Chara globularis, a common, eutrophication-tolerant macroalga, found L. minor domination to inhibit growth of C. globularis and potentially lead to a gradual decline of its overall population (Van Onsem et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…2e), notably through interspecific competition for light. For example, shading by the free‐floating duckweed in a mesocosm experiment modified submerged charophyte morphology and decreased reproductive capacity, resulting in an earlier peak of reproductive organ density (Van Onsem and Triest 2021). Conversely, increased light availability through changes in riparian vegetation canopy associated with stochastic weather events explained an increase in gross primary production by macroalgae in streams altering the overall growing season (Roberts et al 2007; Mulholland et al 2009).…”
Section: Figmentioning
confidence: 99%